Quantifying the relationship between prey density, livestock and illegal killing of leopards. Issue 6 (11th April 2022) - Soofi, Mahmood; Qashqaei, Ali T.; Mousavi, Marzieh; Hadipour, Ehsan; Filla, Marc; Kiabi, Bahram H.; Bleyhl, Benjamin; Ghoddousi, Arash; Balkenhol, Niko; Royle, Andrew; Pavey, Chris R.; Khorozyan, Igor; et al.
Abstract: Many large mammalian carnivores are facing population declines due to illegal killing (e.g. shooting) and habitat modification (e.g. livestock farming). Illegal killing occurs cryptically and hence is difficult to detect. However, reducing illegal killing requires a solid understanding of its magnitude and underlying drivers, while accounting for the imperfect detection of illegal killing events. Despite the importance of illegal killing of large carnivores in comparison with other causes of mortality, its relationship with potential drivers such as livestock density and wild prey abundance is rarely described. Using ranger‐collected data (2007–2019) of leopard killing events and data on covariates (livestock density, wild prey abundance, road length, protected area size, elevation) across Iran, we applied a single‐visit N‐mixture model to jointly model variation in detection probability and expected annualized number of leopard killing events. Over the study period, we estimated 428 leopard mortalities (95% CI 184 to 1, 014), which was 45% larger than the observed number. Expected intensity of leopard killing was positively related to protected area size, livestock density and wild prey abundance. Detection of leopard killing was higher in areas with more developed road networks. Synthesis and applications . Ranger‐based monitoring data on poaching of carnivores are cost effective, but traditional analysis does not take into account imperfect detection. We show that innovative statistics (single‐visit N‐mixture modelling) can reliably quantify poaching events and address their drivers, at large geographical scales. We used the example of the Persian leopard across Iran, but our approach is also applicable to understand killing dynamics of other species. Results suggest that a high frequency of leopard killing is likely to occur in areas with >100 livestock per km 2 and >450 individuals of wild prey per km 2 . This highlights the need for improved management of livestock grazing and effective measures around high‐risk protected areas to mitigate human–leopard conflict and reduce killing of leopards. Abstract : Ranger‐based monitoring data on poaching of carnivores are cost effective, but traditional analysis does not take into account imperfect detection. We show that innovative statistics (single‐visit N‐mixture modelling) can reliably quantify poaching events and address their drivers, at large geographical scales. We used the example of the Persian leopard across Iran, but our approach is also applicable to understand killing dynamics of other species. Results suggest that a high frequency of leopard killing is likely to occur in areas with >100 livestock per km 2 and >450 individuals of wild prey per km 2 . This highlights the need for improved management of livestock grazing and effective measures around high‐risk protected areas to mitigate human–leopard conflict and reduce killing of leopards. Photo: Seyed‐Babak Musavi.